Characteristics of Large-Scale Structures in Supersonic Planar Mixing Layer with Finite Thickness - Hailong Zhang; Jiping Wu; Jian Chen; Weidong Liu (Advances in Mechanical Engineering, 2014)
Nanoparticle-based planar laser scattering (NPLS) experiments and large eddy simulation (LES) were launched to get the fine structure of the supersonic planar mixing layer with finite thickness in the present study. Different from the turbulent development of supersonic planar mixing layer with thin thickness, the development of supersonic planar mixing layer with finite thickness is rapidly. The large-scale structures of mixing layer that possess the characters of quick movement and slow changes transmit to downriver at invariable speed. The transverse results show that the mixing layer is strip of right and dim and possess 3D characteristics. Meanwhile the vortices roll up from two sides to the center. Results indicate that the higher the pressure of the high speed side is, the thicker the mixing layer is. The development of mixing layer is restrained when the pressure of lower speed side is higher. The momentum thickness goes higher with the increase of the clapboard thickness. Through increasing the temperature to change the compression can affect the development of the vortices. The present study can make a contribution to the mixing enhancement and provide initial data for the later investigations.